Estimating the Price and Income Elasticities of Crude Oil Import Demand for Turkey - Ismail Kavaz (International Econometric Review (IER), 2020)
In this study, the price and income elasticities of Turkey's imported crude oil demand are analysed. In this context, annual time series data covering the period 1970-2018 are preferred for imported crude oil, real price for crude oil and real GDP. As known, Turkey is an energy dependent country especially in fossil fuels. Therefore, estimating Turkey's crude oil demand equations is very significant to analyse the consumption trend and the future expectations in terms of this energy resource. This study employs Harvey's Structural Time Series Modelling Method (STSM) with the underlying energy demand trend (UEDT) concept for determining the relations among income, price and crude oil import demand. The empirical results show that the income and price elasticities of crude oil demand in Turkey are 0.66 and -0.11, respectively. The estimated elasticities suggest that income and price elasticities for the imported crude oil demand are inelastic.
Keywords: C22; Q41; 330; Crude Oil Import Demand; Elasticity Estimates; Turkey